ICT and occupation-based measures of organisational change: Firm and employee outcomes - Petri Böckerman; Antti Kauhanen; Mika Maliranta (The Research Institute of the Finnish Economy (ETLA), 2012)
To examine the productivity, employment and wage effects of ICT, we apply novel occupation based measures of organisational change within firms. With these measures, we directly address the complementarities between ICT and organisational changes. Our results support the view that organisational change complements ICT investments in a productivity-enhancing manner. In particular, the ICT-driven productivity gains are associated with the destruction of routine and non-interactive tasks in an organisation. Furthermore, using longitudinal aspects of our linked employer-employee data, we find that whereas ICT does not affect the probability of an employee becoming unemployed, it has a positive impact on the wage growth of retained employees.
Keywords: J24; J31; L23; M51; 330; ICT; innovation; organisational change; restructuring; productivity; performance; wages